If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 34 + -5x = 1 + -8x + 3 Reorder the terms: 34 + 2x + -5x = 1 + -8x + 3 Combine like terms: 2x + -5x = -3x 34 + -3x = 1 + -8x + 3 Reorder the terms: 34 + -3x = 1 + 3 + -8x Combine like terms: 1 + 3 = 4 34 + -3x = 4 + -8x Solving 34 + -3x = 4 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 34 + -3x + 8x = 4 + -8x + 8x Combine like terms: -3x + 8x = 5x 34 + 5x = 4 + -8x + 8x Combine like terms: -8x + 8x = 0 34 + 5x = 4 + 0 34 + 5x = 4 Add '-34' to each side of the equation. 34 + -34 + 5x = 4 + -34 Combine like terms: 34 + -34 = 0 0 + 5x = 4 + -34 5x = 4 + -34 Combine like terms: 4 + -34 = -30 5x = -30 Divide each side by '5'. x = -6 Simplifying x = -6
| 17=1-3b-5b | | 6+(n-4)=2(2n+13) | | 3*x^2+2=50 | | 10h-8h=h+25 | | 18=-4x-2+4 | | 44=4(n+3)+4n | | 3y-20=30 | | 9x8/9 | | 23g=7.13 | | 3x+6=-18-3x | | 4-(p-1)+4p+7=p+4 | | 9+12x=-24+x | | 12x+17=13x+8 | | 2[t-(9-2t)]=4(2t-4) | | 6x+5y-1=10 | | 7x+1=-6+8x | | -24+x=x+13 | | 4x+12=36-6x | | 6(-s-6)-3(6s-3)=s+8+3s | | 193=41*1+0.40x | | -1.4+(-5.7)= | | 6t-24=0 | | X+76+110=180 | | 8x+9(.25x)=10 | | -2+26x=25x | | 4*8.4+8*0.8=40 | | -3-s=4tj+19 | | 8(1.25-1.125x)+9x=10 | | 4*12+8*0.8=40 | | 24=m-15 | | 4*10+8*0.8=40 | | 4*4.6+8*0.8=40 |